Morphological fluctuations of individual mitochondria in living cells - Fernández Casafuz, Agustina B; De Rossi, María Cecilia; Bruno, Luciana (Journal of physics. Condensed matter, 2022)
Uncovering the link between mitochondrial morphology, dynamics, positioning and function is challenging. Mitochondria are very flexible organelles that are subject to tension and compression within cells. Recent findings highlighted the importance of these mechanical aspects in the regulation of mitochondria dynamics, arising the question on which are the processes and mechanisms involved in their shape remodeling. In this work we explored in detail the morphological changes and spatio-temporal fluctuations of these organelles in living Xenopus laevis melanophores, a well-characterized cellular model. We developed an automatic method for the classification of mitochondria shapes based on the analysis of the curvature of the contour shape from confocal microscopy images. A persistence length of 2.1 μm was measured, quantifying, for the first time, the bending plasticity of mitochondria in their cellular environment. The shape evolution at the single organelle level was followed during a few minutes revealing that mitochondria can bend and unbend in the seconds timescale. Furthermore, the inspection of confocal movies simultaneously registering fluorescent mitochondria and microtubules suggests that the cytoskeleton network architecture and dynamics play a significant role in mitochondria shape remodeling and fluctuations. For instance changes from sinuous to elongated organelles related to transitions from confined behavior to fast directed motion along microtubule tracks were observed.